Development and validation of the Gestalt Therapy Fidelity Scale. (18th May 2020) - Fogarty, Madeleine; Bhar, Sunil; Theiler, Stephen
Abstract: Objective: Three studies were conducted to develop and validate the Gestalt Therapy Fidelity Scale (GTFS), a 21-item measure of treatment adherence for Gestalt Therapy (GT). Method: Thirty five items for possible inclusion in the GTFS were generated on the basis of a literature review. In Study 1, a Delphi methodology consulting 63 international GT experts was used to select items for the GTFS. In Study 2, six experts used the scale to rate video-based sessions of GT, and provided feedback on the usability of the scale. In Study 3, 176 participants from 18 countries used the GTFS to rate GT and not-GT video recorded sessions. Results: The Delphi study consensus method resulted in 25 items for consideration in the GTFS. The scoring system and items were subsequently revised following further feedback from experts (Study 2). The GTFS was found to significantly discriminate between GT and not-GT based sessions (Study 3): raters scored GT sessions significantly higher than not-GT sessions. High levels of internal and inter-rater reliability were found. Conclusion: The GTFS is supported as a psychometrically sound measure of treatment adherence for GT, and hence can be used to assess the degree to which therapists are administering GT.